KARAKTERISTIK VELVA BUAH ALPUKAT DENGAN PENAMBAHAN GULA AREN SEBAGAI PENAMBAH CITA RASA - Ismail Haridsyah; Vonny Setiaries Johan; Fajar Restuhadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
Velva is one type of dessert that has a low-fat content. The utilization of avocado as a product in the form of velva is expected to extend the shelf life of avocados and make avocados into other processed products.. One of the ingredients that can be used is the addition of palm sugar. This study aims to obtain the best formulation with the addition of palm sugar as a taste in the making of avocado velva. This research was conducted experimentally using a completely randomized design with 4 treatments and 4 replications to obtain 16 experimental units. The treatment in this study was the comparison of avocado pulp and palm sugar as follows: P1 (100:0); P2 (90:10); P3 (80:20); P4  (70:30). The parameters observed in this study are overrun, melting time, total dissolved solids, and descriptive and hedonic sensory assessment of color, aroma, taste, and softness. The best treatment was the P2 treatment which used a combination of avocado and palm sugar 90:10 with total dissolved solids of 21.2708 °Brix, melting time of 12.57 minutes, overrun of 19.5736%. The results showed that the different ratios of avocado and palm sugar affected melting time, overrun, and total dissolved solids.Keywords: Velva; Brown Sugar, Avocado..